Application of Remote Sensing and Geographic Information Systems on Water Resources Management - A. N. Amadi; H. O. Nwankwoala (Global Journal of Earth Science and Engineering, 2017)
Water is a primary source of life and is required in sufficient quantity and acceptable quality to sustain all human activities such as domestic, agricultural and industrial needs. This requirement however, is hardly fulfilled due to various natural and anthropogenic activities. Remote sensing and Geographic Information System (GIS) techniques are useful in hydrological research and applications. Remote sensing observations enable improved characterization of the land surface which are relevant in hydrological studies. Remote sensing with its merits of providing spatially extensive, multi-temporal and cost effective data, has become a very handy tool in identifying hydrogeological processes. These studies have revealed the application of integrated remote sensing and GIS technologies in groundwater exploration and exploitation. Integrated remote sensing and GIS are widely used in groundwater mapping. Locating potential groundwater targets is becoming more convenient, cost effective than invasive methods and efficient with the advent of a number of satellite imagery. The nature of remote sensing-based groundwater exploration is to delineate all possible features connected with localization of groundwater. Data, driven out of remote sensing, support decisions related to sustainable development and groundwater management. Integration of remotely sensed data, GPS, and GIS technologies provides a valuable tool for monitoring and assessing water pollution. Remotely sensed data can be used to create a permanent geographically located database to provide a baseline for future comparisons hydrological studies. The integrated use of remotely sensed data, GPS, and GIS will enable consultants and natural resource managers to develop management plans for a variety of natural resource management applications.